Inducción de supresividad a fitopatógenos del suelo. Una estrategia para la transición agroecológica en horticultura - De Luca, Laura Cecilia; Perez, Maximiliano (European Scientific Institute (ESI), 2025)
Abstract: Suppressiveness of soil-borne disease, as been tried unsuccessfully from a reductionist approach, which seeks to control soil biologically - based diseases with specific strains of antagonistic microorganisms. For this study we selected two genetics lines of tomato: a variety called UCO PLATA and a hybrid, ELPIDA. To stimulate and evaluate the suppressive effect two types of treatments were carried out: 1) Biostimulated (Pbio) substrat prepared with earthworm humus and forest litter intent to amplify beneficial soil functional groups; 2) Conventional (Pcon) under the standard technique used. The influence of biostimulation seems to accompany the crop to harvest, but varies according to the treatment performed on the ground. The differences between the microbiological parameters taken as suppressiveness indicators show no major differences considering the hybrid and variety, therefore we can not conclude on the possible influence of plant genetics on suppressive effect.